High-intensity lasers and research activities in China - Li, Yutong; Chen, Liming; Chen, Min; Liu, Feng; Gu, Yuqiu; Guo, Bing; Hua, Jianfei; Huang, Taiwu; Leng, Yuxin; Li, Fei; Li, Lu; Li, Ruxin; et al. (High power laser science and engineering, 2025)
This paper provides an overview of the current status of ultrafast and ultra-intense lasers with peak powers exceeding 100 TW and examines the research activities in high-energy-density physics within China. Currently, 10 high-intensity lasers with powers over 100 TW are operational, and about 10 additional lasers are being constructed at various institutes and universities. These facilities operate either independently or are combined with one another, thereby offering substantial support for both Chinese and international research and development efforts in high-energy-density physics.